The Analysis of Inpatients Satisfaction on Service Quality At Yogyakarta Respira Hospital - Dahyanto Dahyanto; Fitri Arofiati (Universitas Muhammadiyah Yogyakarta, 2018)
Health service quality is the level of perfection of health services that are organized in accordance with the code of ethics and service standards, so as to give satisfaction for each patient. This study aims to analyze the satisfaction of inpatients in the disease section at Respira Yogyakarta Hospital. Method: Mix-method research with a case study design. The quantitative samples are questionnaires (March - April 2017, n = 9). And the qualitative samples are lung specialists, nurses, nutritionists and people who are involved in patient satisfaction (n = 30) taken using purposive sampling technique. Results: Input: Inpatients at RS Respira Yogyakarta are satisfied. This hospital plays a role in the quality of health services. One of its ways is to provide the amount of equipment in Inpatient Installation according to the needs of patients, both in terms of its quality and quantity. Process: Development of patient satisfaction has involved the health service quality team. Obstacles are still in the way in fulfilling patient satisfaction including non-routine satisfaction surveys, uneven knowledge, lack of ownership, low of professionalism, evaluation of patient satisfaction is not done routinely. Output: Patients feel satisfied with the service at Respira Yogyakarta Hospital. Conclusions: The result of this research is that inpatients at Respira Yogyakarta Hospital are satisfied.